Men without women : stories - Murakami, Haruki; Gabriel, Philip, 1953-; Goossen, Ted (London : Vintage ; Harvill Secker, 2017)
THE SUNDAY TIMES BESTSELLERAcross seven tales, Haruki Murakami brings his powers of observation to bear on the lives of men who, in their own ways, find themselves alone. Here are vanishing cats and smoky bars, lonely hearts and mysterious women, baseball and the Beatles, woven together to tell stories that speak to us all.
Drive my car -- Yesterday -- An independent organ -- Scheherazade -- Kino -- Samsa in love -- Men without women.
ENH
Keywords: Murakami, Haruki, -- 1949- -- Translations into English; Men -- Identity -- Fiction; Short stories, Japanese -- 20th century; Japan -- Social life and customs -- Fiction